An Analysis of the Implementation of DSN–MUI Fatwas on Pawn-Based Products in Pegadaian’s Public Documentation - Khoirul Muhtadin; Ikhwan Ansori (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Public documentation is vital for transparency and Shari’ah compliance in Islamic finance, especially for collateral (rahn)-based products. This study examines the alignment between Pegadaian’s pawn-based products and DSN-MUI fatwas (No. 25/2002, 26/2002, 68/2008, 92/2014), and how information inconsistencies affect compliance perceptions. Through qualitative document analysis of Pegadaian’s websites and relevant fatwas, the research identifies substantial inconsistencies. These include mismatches between product labels and underlying contracts, varied calculations for mu’nah (benefit fees), and inaccurate terminology in products like Cicil Kendaraan and Arrum BPKB. Such issues blur contractual boundaries, risk misleading consumers on Shari’ah-compliant fees, and indicate weak digital content governance. The findings emphasize that true Shari’ah compliance must be evident not only internally but also in all public-facing information. Clarity, accuracy, and standardization in documentation are crucial for maintaining consumer trust and institutional legitimacy, highlighting the need for improved governance and oversight.